Intervensi Permen Hard Candy Dengan Kandungan Teh Hitam Dan Sorbitol Untuk Penurunan Skor Plak Anak-Anak Usia Sekolah - Lisa Prihastari (Lembaga Penelitian Universitas YARSI, 2022)
Background: The use of black tea as an anti-plaque and anti-caries material is still very limited in Indonesia. Various studies have shown the benefits of black tea which can reduce plaque scores, increase fluoride levels and inhibit the growth of Streptococcus mutans bacteria. The innovation of black tea in the form of candy is expected to be liked by children and does not eliminate its benefits as an alternative to anti-cariogenic ingredients. Objective: To determine the difference in effectiveness between consuming black tea candy with sorbitol and placebo candy (sorbitol only) in reducing plaque accumulation. Methods: This study is a experimental using a Randomized Controlled Clinical Trials (RCT) design and a single blind method. The research subjects consisted of 42 students at SDN 019 Cempaka Putih and SDN 03 Pagi Pasar Minggu, aged 7-8 years. The sample was selected based on the inclusion criteria of the study. The examination was carried out to determine plaque scores using the Loe and Sillness index and pufa index scores which were measured in 3 measurement times, namely day 1, day 7 and day 23. Results: The average PUFA index of research subjects was 1,05. The results of this study showed that there was a significant decrease in plaque scores in each group before and after consuming sweets on the 1st day, 7th day and 23rd day measurement (p-value 0.05). In the black tea group, there was a greater reduction in plaque scores than the placebo group.. Conclusion: Consuming black tea candy compared to placebo candy containing sorbitol had the same effectiveness in reducing plaque scores.